Air Pollution and Lung Cancer - Ida Ayu Jasminarti Dwi Kusumawardani; Putu Gita Indraswari; Ni Luh Gede Yoni Komalasari (Faculty of Medicine Universitas Airlangga, 2023)
Malignant lung cancer is the leading cause of cancer-related death worldwide. Smoking is the main risk factor for lung cancer. However, the International Agency for Research on Cancer (IARC) declared in 2013 that outdoor air pollution is a substance that is carcinogenic and contributes to lung cancer. This was supported by several studies which show an increased prevalence of adenocarcinoma, even in countries with a low prevalence of smokers. The presence of one or more substances in the air for longer periods or at higher concentrations than usual, which can potentially have negative effects, is called air pollution. Aside from carbon monoxide (CO), nitrogen dioxide (NO2), lead, ozone (O3), and sulfur dioxide (SO2), particulate matter with <2.5 µm diameter (PM2.5) has been identified to be associated with the risk of lung cancer. The risk of lung cancer was higher after prolonged exposure to PM2.5 regardless of age, gender, and smoking history. Exposure to air pollution is a significant factor in the onset and progression of lung cancer. Oxidative stress, deoxyribonucleic acid (DNA) damage, inflammation, metabolism, epigenetic control, and signal transduction pathways are a few potential mechanisms of air pollution-induced lung cancer. Everyone, including the government and the general public, must implement strategies to stop the harmful effects of air pollution.